Narratives of power: Bringing ideology to the fore of planning analysis. (February 2020) - Shepherd, Edward; Inch, Andy; Marshall, Tim
This Special Issue starts from the premise that the concept of ideology holds significant analytical potential for planning but that this potential can only be realised if ideology is brought to the fore of analysis. By naming ideology and rendering it visible, we hope to bring it out from the shadows and into the open to examine its value and what it can tell us about the politics of contemporary planning. The articles in this Special Issue therefore seek to contribute to established academic debates by exploring some of the ways ideology can be deployed as a tool in the analysis of planning problems. This article introduces the Special Issue by exploring the various accounts in the articles of (1) what ideology is; (2) what its effects are; (3) where ideology may be identified and (4) what different theories of ideology can tell us about planning. There inevitably remain many un-answered questions, paths not taken and debates left unaddressed. We hope other scholars will be inspired (or provoked) to address these omissions in the future.